Performance of Male Layer Fed Ration Containing Green Algae (Spirogyra jaoensis) Extract - A. R. Ramadhanti; N. O. J. Puspita; C. F. Refalta; H. Kurnianto; H. T. S. Saragih (Faculty of Animal Science, Bogor Agricultural University, 2021)
Some plant extracts containing natural antimicrobial compounds can be used as either feed supplements or alternatives to antibiotic growth promoters (AGP). A plant known as green algae (Spirogyra jaoensis), is one of the species of green algae group. This study aimed to determine the effect of feeding a diet containing S. jaoensis ethanolic extract on the performance of male layer. A complete randomized model was used for experimental design in various variables. This study was conducted with 240 male layer day-old chick (DOC) (31.0±1.25 g) divided into 5 treatment groups. Each group consisted of 48 birds, with 3 replicates and 16 birds for each replicate. Dietary treatments tested namely, Con: control (without S. jaoensis), EGA1: Con + S. jaoensis extract at 0.05%, EGA2: Con + S. jaoensis extract at 0.1%, EGA3: Con + S. jaoensis extract at 0.25%, and EGA4: Con + S. jaoensis extract at 0.5%. Three chickens from each triplicate were taken and decapitated on the neck and the surgery was performed for histological preparations. The variables observed were villi height, cryptic depth, villi/crypt ratio, goblet cell area of the small intestine, thymus organ weight, myofiber area, fasciculus area, muscle surface area of Pectoralis thoracicus muscle, and growth performance in 14-day-old chickens. Data were subjected to one-way analysis of variance (ANOVA). If it was significant, a Tukey-test was performed with a significance level at p≤0.05. The results showed that small intestinal morphology, muscle morphology, and growth performance of the EGA4 chicken group increased significantly compared to controls (p≤0.05). This study concludes that the administration of S. jaoensis ethanolic extract improves morphology of the small intestine, morphometry of thymus organs, Pectoralis thoracicus muscle performance, and growth performance in male layer.